Peace Resolution Mechanism Related to Discipline and Code of Ethics Violations of the Police Profession in the Jurisdiction of the North Sumatera Regional Police - Chalid Sitorus; Isnaini Isnaini; Wenggedes Frensh (Journal La Sociale, 2025)
This study aims to analyze the peace settlement mechanism related to violations of discipline and the code of ethics of members of the Police profession in the jurisdiction of the North Sumatera Regional Police based on the Regulation of the Head of Division (Perkadiv) of the National Police Number 4 of 2021 concerning Procedures for Peace Settlement in Violations of Discipline and the Code of Ethics of the National Police Profession. The research method used is normative juridical with a qualitative approach, which involves analysis of laws and regulations, official documents, and interviews with related parties. The results of the study indicate that the peace settlement mechanism in Perkadiv Polri Number 4 of 2021 emphasizes the principles of justice, compliance, and professionalism in handling violations of discipline and the code of ethics. The settlement process involves stages of mediation, evaluation, and decision-making involving various parties, including direct superiors and the ethics committee. However, several obstacles were found in its implementation, such as the lack of socialization and even understanding among members of the National Police. This study recommends the need to increase socialization, training, and supervision to ensure that the peace settlement mechanism runs effectively and in accordance with the objectives of enforcing discipline and the code of ethics of the profession within the North Sumatera Regional Police.